GIS and Remote Sensing to Support Precision Viticulture for Analysis of Vineyards in the Campanha Wine Region, Brazil. - HOFF, R. (2017)
Agricultural products depend upon the geographical area of production and their quality depends on environment and crop management. Grapevine cultivars can be adapted to the environment, resulting in differences in fruit quality, which will produce different wines. The knowledge of the territory gives value to agricultural products and the use of free software has advantages to associate spatial data with Geographical Information System (GIS) functions for Digital Image Processing (DIP), spatial analysis, Digital Elevation Models (DEM) and databases. The objective of this study was analyze spatially vineyards of Vitis vinifera in south Brazil, using DEM for zoning landscape and employing RapidEye images at different crop stages, in order to follow the Normalized Difference Vegetation Index (NDVI) and test tools that allow the producer a customized management between vineyards and within each vineyard. The software gvSIG was used to evaluate NDVI for plant vigor in order to infer diseases, water status, and other factors. NDVI, altitude, slope, and exposure average were generated for 64 vineyards. To a Cabernet Sauvignon area, a map was generated, showing the variability of the vineyard by resampling of pixel size image, from five to one-meter spatial resolution and zoning according to critical variables for the vineyard. In conclusion, geotechnology is important for viticulture, as a support to environmental diagnostics and are a strategic application for agricultural management. Analytical tools and sensors can provide fast, easily accessible data to all users, being a technology prone to be of widespread access for the end user.